2021
DOI: 10.1037/apl0000926
|View full text |Cite
|
Sign up to set email alerts
|

The influence of COVID-induced job search anxiety and conspiracy beliefs on job search effort: A within-person investigation.

Abstract: New labor market entrants face significant hurdles when searching for a job, with these stressors likely amplified during the COVID-19 pandemic. Here, we consider how COVID-induced job search anxietyfeeling anxious about one's job search due to issues imposed by the pandemic-has the potential to affect adaptive, goal-directed efforts, and maladaptive, goal-avoidant reactions. We theorize that this anxiety can prompt job seekers to engage in problem-solving pondering and affect-focused rumination, with these ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
32
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 70 publications
5
32
3
Order By: Relevance
“…This subscale includes questions about an individual's plans to seek for a job. Our results, thus, are in line with findings by Gabriel et al (Gabriel et al, 2021) who found that the endorsement of CTs hampers efforts put in searching for a dream job. Perhaps, this could be partially explained by negative forecasts about future economic development.…”
Section: Cts Undermine the Relation Between Precariaty And Adaptive F...supporting
confidence: 93%
See 1 more Smart Citation
“…This subscale includes questions about an individual's plans to seek for a job. Our results, thus, are in line with findings by Gabriel et al (Gabriel et al, 2021) who found that the endorsement of CTs hampers efforts put in searching for a dream job. Perhaps, this could be partially explained by negative forecasts about future economic development.…”
Section: Cts Undermine the Relation Between Precariaty And Adaptive F...supporting
confidence: 93%
“…Finally, there is preliminary evidence that the endorsement of CTs could have negative effects on an individual's economic performance. For instance, Gabriel et al (2021) found out that the belief in CTs hinders the quality of job search activities. Undergraduates who were already anxious about job market opportunities and also believed in CTs put less effort in seeking a dream job that could help them to improve their economic situation and increase chances of obtaining interesting job offers.…”
Section: Willingness To Adapt Financial Behaviourmentioning
confidence: 99%
“…Belief in COVID-19 conspiracies predicted higher fear, distress, and anxiety ( Chen et al, 2020 ; Jolley et al, 2020b ; Jovančević and Milićević, 2020 ; Leibovitz et al, 2021 ), future anxiety ( Duplaga and Grysztar, 2021 ), and also lower wellbeing ( Spasovski and Kenig, 2020 ; van Prooijen et al, 2021 ; Freeman et al, 2022 ) and life satisfaction ( Kohút et al, 2022 ). These implications are also visible in the working environment in the form of a negative impact of CBs on job search behavior ( Gabriel et al, 2021 ) and lower job satisfaction ( Chen et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…The researchers also found that job applications were substantially greater in both periods for remote working jobs, in comparison with face‐to‐face and organization‐based jobs, indicating perhaps some safety concerns with regard to the pandemic crisis in employees' job‐related choices. Gabriel et al (2021) extended this research by examining how individuals engaged in different types of job search‐related behaviors. In particular, the researchers found that job search‐related anxiety during the COVID‐19 pandemic crisis promoted individuals' problem‐solving pondering, and in turn, fostered dream (effort in pursuing one's dream job), focused (effort in pursuing a selection of carefully screened jobs), and exploratory (effort toward exploring a wide range of jobs) job search efforts.…”
Section: Setting the Scene: What Have We Learned About Organizational...mentioning
confidence: 99%